Hydrophobically Grafted Pullulan Nanocarriers for Percutaneous Delivery: Preparation and Preliminary In Vitro Characterisation - Bostanudin, Mohammad F.; Barbu, Eugen; Liew, Kai Bin (Polymers, 2021)
Polymeric colloidal nanocarriers formulated from hydrophobically grafted carbohydrates have been the subject of intensive research due to their potential to increase the percutaneous penetration of hydrophilic actives. To this goal, a series of hydrophobically grafted pullulan (BMO-PUL) derivatives with varying degree of grafting (5–64%) was prepared through functionalisation with 2-(butoxymethyl)oxirane. The results demonstrated that monodispersed BMO-PUL nanocarriers (size range 125–185 nm) could be easily prepared via nanoprecipitation; they exhibit close-to-spherical morphology and adequate stability at physiologically relevant pH. The critical micellar concentration of BMO-PUL was found to be inversely proportional to their molecular weight (Mw) and degree of grafting (DG), with values of 60 mg/L and 40 mg/L for DG of 12.6% and 33.8%, respectively. The polymeric nanocarriers were loaded with the low Mw hydrophilic active α-arbutin (16% loading), and the release of this active was studied at varying pH values (5 and 7), with a slightly faster release observed in acidic conditions; the release profiles can be best described by a first-order kinetic model. In vitro investigations of BMO-PUL nanocarriers (concentration range 0.1–4 mg/mL) using immortalised skin human keratinocytes cells (HaCaT) evidenced their lack of toxicity, with more than 85% cell viability after 24 h. A four-fold enhance in arbutin permeation through HaCaT monolayers was recorded when the active was encapsulated within the BMO-PUL nanocarriers. Altogether, the results obtained from the in vitro studies highlighted the potential of BMO-PUL nanocarriers for percutaneous delivery applications, which would warrant further investigation in vivo.